Dynamic biomechanical equilibrium in pelvic organ prolapse: from mechanistic insights to precision reconstruction - Tian, Daoming; Luo, Qian; Wang, Xingqi; Wen, Yubin; Li, Yuan; Gu, Jiangna; Li, Hongcheng; Shen, Jihong; Li, Ling (Frontiers in Medicine, 2025)
BackgroundThe traditional treatment of pelvic floor organ prolapse (POP) is based on static anatomical repair, but the postoperative recurrence rate is still high in the surgical rate, which suggests the need to re-examine its pathogenesis from a biomechanical perspective.ObjectiveTo propose a new concept of POP prevention and treatment centered on the dynamic mechanical balance system of the levator plate-perineum and posterior vaginal vault, and to provide a theoretical basis for clinical intervention.ResultsThis study reveals the key mechanisms of the pelvic floor dynamic balance system through biomechanical analysis. The stability of the pelvic floor is maintained by three synergistic aspects: first, the triangular support structure composed of the bladder-uterus-tibial plate realizes effective stress transmission; second, the posterior fornix of the vagina serves as a mechanical fulcrum, guiding the uterus to produce the characteristic “downward-backward” displacement; and lastly, the 90° functional folding angle of the vagina ensures the reasonable distribution of the loads. When this sophisticated system becomes unbalanced due to birth injury or aging, it leads to abnormal stress transmission and organ displacement, ultimately leading to prolapse symptoms.ConclusionShifting from static repair to dynamic mechanical balance reconstruction is the key to improving POP efficacy, and individualized mechanical repair strategies and long-term maintenance mechanisms need to be further explored in the future.